Biotechnology to Combat COVID-19 2022
DOI: 10.5772/intechopen.99100
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ex-Vivo/3D Organoid Models in COVID-19 Research

Abstract: COVID-19 treatment methods based on 3D organoids and ex-vivo platforms are analyzed in this chapter. Initially, the platforms available for cell culture and its working characteristics are explained. Subsequently discusses the organoids with their definition and included their uses in various applications. Further, the chapter extends to describe the uses of different organoids with their use in different stages. Most of these methods utilized the 3D ex-vivo cell culture method to develop organoids and test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These models have been suggested as a prominent platform to gain a fundamental understanding of viral infections such as COVID-19 ( Basanthakumar, 2021 ; de Melo et al, 2021 ; Deguchi et al, 2021 ; Harb et al, 2022 ; Kronemberger et al, 2021 ; Lv et al, 2021 ; Ramani et al, 2021 ; Sia et al, 2022 ; Sourimant et al, 2022 ; van der Vaart et al, 2021 ; Wang et al; Yu, 2021 ; Zech et al, 2021 ) and could be a good alternative to facilitate the development and discovery of new therapeutics and vaccines ( Clevers, 2020 ; Raimondi et al, 2020 ). To date, various types of organoid-enabled 3D models have been employed to study and understand SARS-CoV-2 infection such as the brain organoid ( Ramani et al, 2020 ), lung organoid ( Ekanger et al, 2022 ; Salahudeen et al, 2020 ; van der Vaart et al, 2021 ; Wang et al, 2021a ), intestine organoid ( Dickson, 2020 ), as well as liver ductal organoid and bile duct organoid ( Zhao et al, 2020a ) ( Fig.…”
Section: In Vitro Tissue Models and Technologies For Covid-1...mentioning
confidence: 99%
“…These models have been suggested as a prominent platform to gain a fundamental understanding of viral infections such as COVID-19 ( Basanthakumar, 2021 ; de Melo et al, 2021 ; Deguchi et al, 2021 ; Harb et al, 2022 ; Kronemberger et al, 2021 ; Lv et al, 2021 ; Ramani et al, 2021 ; Sia et al, 2022 ; Sourimant et al, 2022 ; van der Vaart et al, 2021 ; Wang et al; Yu, 2021 ; Zech et al, 2021 ) and could be a good alternative to facilitate the development and discovery of new therapeutics and vaccines ( Clevers, 2020 ; Raimondi et al, 2020 ). To date, various types of organoid-enabled 3D models have been employed to study and understand SARS-CoV-2 infection such as the brain organoid ( Ramani et al, 2020 ), lung organoid ( Ekanger et al, 2022 ; Salahudeen et al, 2020 ; van der Vaart et al, 2021 ; Wang et al, 2021a ), intestine organoid ( Dickson, 2020 ), as well as liver ductal organoid and bile duct organoid ( Zhao et al, 2020a ) ( Fig.…”
Section: In Vitro Tissue Models and Technologies For Covid-1...mentioning
confidence: 99%
“…In [ 6 ], the authors reported that the World Health Organization classified the virus as an epidemic during its early stages, emphasizing its severity. Understanding the potential scale of COVID-19 cases is crucial for effective reaction and management, given the global impact of the pandemic and the absence of an apparent cure.…”
Section: Introductionmentioning
confidence: 99%